2023
DOI: 10.34133/remotesensing.0049
|View full text |Cite
|
Sign up to set email alerts
|

Recipes for the Derivation of Water Quality Parameters Using the High-Spatial-Resolution Data from Sensors on Board Sentinel-2A, Sentinel-2B, Landsat-5, Landsat-7, Landsat-8, and Landsat-9 Satellites

Abstract: Satellites have provided high-resolution ( < 100 m) water color (i.e., remote sensing reflectance) and thermal emission imagery of aquatic environments since the early 1980s; however, global operational water quality products based on these data are not readily available (e.g., temperature, chlorophyll- a , turbidity, and suspended particle matter). Currently, because of the postprocessing required, only users with expressive experience can exploit these data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 470 publications
(670 reference statements)
0
10
0
Order By: Relevance
“…Távora et al also suggested that Patos Lagoon exhibits optical properties that differ from those considered in the semi-analytical algorithm of Nechad et al [27]. Thus, the study area could serve as a case study for the regionality of turbidity and SPM estimates, which was addressed in previous works [10,34] by regionally recalibrating the coefficients of the turbidity algorithm for Landsat 5, 7, and 8. Therefore, we also provided regionally recalibrated coefficients specific to the study area, expanding this work to include SPM and other satellites, applying a more robust recalibration method, and examining the improvements and limitations associated with this approach.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Távora et al also suggested that Patos Lagoon exhibits optical properties that differ from those considered in the semi-analytical algorithm of Nechad et al [27]. Thus, the study area could serve as a case study for the regionality of turbidity and SPM estimates, which was addressed in previous works [10,34] by regionally recalibrating the coefficients of the turbidity algorithm for Landsat 5, 7, and 8. Therefore, we also provided regionally recalibrated coefficients specific to the study area, expanding this work to include SPM and other satellites, applying a more robust recalibration method, and examining the improvements and limitations associated with this approach.…”
Section: Introductionmentioning
confidence: 95%
“…This choice was based on previous comparisons of these two methods, showing that they have distinct spectral uncertainties [11] and performances for different final products [25]. In Patos Lagoon, previous works have applied ACOLITE [10,42] and POLYMER [34], but without a direct comparison of these methods. Additionally, [10] lists the advantages and limitations of each correction.…”
Section: Atmospheric Correctionmentioning
confidence: 99%
See 3 more Smart Citations